A Review of Literature Research on Influencing Factors of Chinese Students Studying Abroad - Zhao, Qianqing; Ooi Boon Keat; Ali Khatibi; Jacqueline Tham (International Journal of Social Sciences and Public Administration, 2025)
The decision to study abroad is a complex process influenced by a multitude of factors spanning individual, familial, societal, and geopolitical dimensions. As the largest source of international students globally, Chinese students' choices and motivations for studying abroad have garnered significant attention from scholars, policymakers, and educational institutions. This article provides a comprehensive review of the existing literature on the factors influencing Chinese students' decisions to study abroad, synthesizing insights from theoretical frameworks such as the push-pull theory, the theory of planned behavior (TPB), and decision-making models. The review highlights the evolving dynamics of international education in the context of globalization, the COVID-19 pandemic, and the shifting preferences toward Asian study destinations. By integrating empirical studies and theoretical perspectives, this article underscores the interplay between structural constraints (e.g., domestic academic competition) and aspirational drivers (e.g., career advancement). The findings emphasize the need for adaptive strategies to address emerging trends such as digital globalization, regionalization of education, and post-pandemic mobility patterns. This review serves as a critical resource for stakeholders aiming to enhance the attractiveness of study destinations and support the holistic development of international students.